LIKUIDITAS PERUSAHAAN, SENSITIVITAS ARUS KAS, DAN KEPUTUSAN INVESTASI - , Destria Kurnianti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to examine the effect of corporate liquidity to investment decision moderated by the level of cash flow sensitivity using non financial companies listed on Stock Exchange from period 2005-2009, consist of 164 companies with 328 observastions.The results of this study are: First, corporate liquidity has positive and significant effect on investment decisions. Second, the level of cash flow sensitivity moderates the relationship between cash flow and investment decisions causing nonmonotonic relationship and U-shape curve. Companies with sensitive cash flow, characterized with young, small, and high growth opportunities have a negative relationship between corporate liquidity and investment decisions. While companies with insensitive cash flow characterized with older and bigger have a positive relationship between corporate liquidity and investment decision.